2009
DOI: 10.1007/s10616-009-9225-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrine suppresses breast cancer cell proliferation and invasion via VEGF-Akt-NF-κB signaling

Abstract: Matrine has shown therapeutic and/or adjuvant therapeutic effects on the treatment of some patients with breast cancer. However, its mechanisms of action are largely unknown. To disclose the mechanisms, we investigated in vitro and ex vivo effects of matrine on the cancer cells. Our results confirmed that matrine significantly suppressed the proliferation of highly-metastatic human breast cancer MDA-MB-231 cell line. Matrine displayed synergistic effects with existing anticancer agents celecoxib (the inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 21 publications
7
102
0
Order By: Relevance
“…Activation of p-Akt and the NF-jB/Bcl-2 pathway leads to inhibition of chemotherapy-induced apoptosis, which results in treatment resistance (Wang et al 1996). Our previous results confirmed that suppression of Akt and the NF-jB/Bcl-2 pathway by anticancer agents inhibited growth and induced apoptosis and cell cycle arrest in A549 cells and breast cancer MDA-MB-231 cells (Wang et al 2009;Yu et al 2009). In the present study, we indicated that bufalin and the inhibitor of PI3 K/Akt (LY294002) and of NF-jB (Bay) inhibited the A549 cell proliferation and the PI3 K/Akt and NF-jB pathway by suppressing the phosphorylation and expressions of Akt and NF-jB and activating the apoptotic pathway of Bcl-2/Bax-mitochondrial-caspase-3 in A549 cells.…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Protein supporting
confidence: 69%
See 2 more Smart Citations
“…Activation of p-Akt and the NF-jB/Bcl-2 pathway leads to inhibition of chemotherapy-induced apoptosis, which results in treatment resistance (Wang et al 1996). Our previous results confirmed that suppression of Akt and the NF-jB/Bcl-2 pathway by anticancer agents inhibited growth and induced apoptosis and cell cycle arrest in A549 cells and breast cancer MDA-MB-231 cells (Wang et al 2009;Yu et al 2009). In the present study, we indicated that bufalin and the inhibitor of PI3 K/Akt (LY294002) and of NF-jB (Bay) inhibited the A549 cell proliferation and the PI3 K/Akt and NF-jB pathway by suppressing the phosphorylation and expressions of Akt and NF-jB and activating the apoptotic pathway of Bcl-2/Bax-mitochondrial-caspase-3 in A549 cells.…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Protein supporting
confidence: 69%
“…Flow cytometry for cell cycle analysis and apoptosis These were done according to our published methods (Wang et al 2009;Yu et al 2009;Zhang et al 2000). In brief, A549 cells were treated for 48 h with bufalin at concentrations of 0, 2.5, 5, and 10 lM.…”
Section: Cell Culture and In Vitro Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry for cell cycle analysis and apoptosis These were done according to our published methods (Wang et al 2009;Yu et al 2009;Zhang et al 2000Zhang et al , 2012a. In brief, LLC cells were treated for 48 h with sodium valproate (VPA, 0.5 mM), coumarin-3-carboxylic acid (HCCA, 0.064 mM), or in combination of VPA (0.5 mM) and HCCA (0.064 mM).…”
Section: Cell Culture and In Vitro Proliferation Assaymentioning
confidence: 99%
“…Matrine has been reported to inhibit human cancer cell migration, adhesion and proliferation by inhibiting the phosphorylation of VASP [6,8,[16][17][18] . However, the precise mechanism by which matrine acts directly on VASP remains unknown.…”
Section: Introductionmentioning
confidence: 99%